How universities promote economic growth - Yusuf, Shahid, 1949-; Nabeshima, Kaoru (Directions in development (Washington, D.C.), 2007)
With the competitiveness of firms in an open and integrated world environment increasingly reliant on technological capability, universities are being asked to take on a growing role in stimulating economic growth. Beyond imparting education, they are now viewed as sources of industrially valuable technical skills, innovations, and entrepreneurship. Developed and developing countries alike have made it a priority to realize this potential of universities to spur growth, a strategy that calls for coordinated policy actions.